The Samurai Strategy - Hoover, Thomas, 1941- (Salt Lake City, UT : Project Gutenberg, 2010)
"The Samurai Strategy" by Thomas Hoover is a financial thriller that was likely written in the late 20th century. The story revolves around Matthew Walton, a freelance corporate takeover lawyer in New York, as he becomes embroiled in a high-stakes scenario involving international finance, murder, and Japan's growing economic power. This intricate tale unfolds against the backdrop of a looming financial crisis, and it explores themes of ambition, loyalty, and personal conflict. The opening of the novel introduces Matthew Walton, who is contemplating a vacation with his daughter while also juggling his law practice. He receives an unusual call from Matsuo Noda, a mysterious Japanese industrialist, who hires him to look into acquiring a significant property in New York. As Walton prepares for an auction at Sotheby$1 (Bs, he reflects on his past relationships and professional life. The section richly describes his character as someone caught between personal loss and professional ambition. It sets the stage for a suspenseful intersection of legal maneuvering and the dark undercurrents of international finance, hinting at a larger, potentially dangerous conspiracy involving Noda and the implications of a huge financial scheme that could have dire repercussions for the U.S. economy. (This is an automatically generated summary.)s
Release date is 2010-11-14
Produced by Al Haines
Keywords: Mystery fiction